La paideia di Odisseo - Elsa Maria Bruni (Firenze University Press, 2019)
The article explores Homer's paideia, which is considered to have established the foundation of the educational principles that still govern European culture today. The historical and educational dimension of the survey is enhanced by the attempt to continually illuminate the research in terms of the origins, motives and meanings of the spirit of Western education and here finds a precise specialization in the determination to identify and evaluate those aspects linked to the formative stages of man and understand more fully the complex traumas of the human and educational realities of today. Thus, after highlighting the traces of weakness in the theoretical and rational approach of Western education through the education of the hero of the Iliad, the investigation focuses on the Odyssey's paideia, in which, as the representation of an alternative educational approach to the logic of pure reason and human perfection, are explored the signs of a new consciousness that has developed on the margins of the history of civilisation revealing more anthropological than postmodernist features.